Burnout: prevalence and associated factors in doctors and nurses in seven regions of Peru - Solís-Cóndor, Risof (2017)
Introduction: Burnout is a multi-causal clinical syndrome considered to be a very important work-related injury and should be identified and analyzed in health professionals given their role in society. Objective: To determine the prevalence and associated factors to burnout in doctors and nurses in seven regions of Peru. Design: Cross-sectional study. Setting: Regions of Apurímac, Ayacucho, Huancavelica, Lima-Callao, Loreto, Piura and San Martín. Participants: 958 physicians and 840 nurses. Interventions: A self-created survey, that included sociodemographic and labor variables, was conducted and the Maslach test was self-applied. The sample was probabilistic, complex, two-stage and stratified. The descriptive analysis used measures of central tendency and percentages, whereas Chi2, Fisher, Anova and Kruskal-Wallis tests were used for the associations. The significance level was ≤ 0.05. Main outcome measures: Prevalence of burnout. Results: The burnout prevalence was 5.5%. High risk of despersonalization (18.7%), emotional exhaustion (10%) and poor personal accomplishment (32.1%) were found. Medical profession (OR = 2.829), male sex (OR = 2.474), family separation (OR = 1.697), dissatisfaction with working hours (OR = 2.609), disease worsened or caused by work (OR = 3.120), and working in local level II (OR = 2.421) or III (OR = 3.363) were associated factors. Conclusions: An association between burnout and work activity in health facilities of greater complexity where the emotional load by the attention of complex cases would be greater was found. Familiar separation or morbidity aggravated or caused by work were stressing factors probably associated to burnout.